Upaya Penggunaan Aplikasi Nike Training Club (NTC) untuk Meningkatkan Kelincahan (Agility) pada UKM Bola Basket STKIP Bina Mutiara - Faiz Faozi; Irpan Abdurahman; Rafdlal Saeful Bakhri; Chairul Umam Ramadhan; Moch Latif; Debi Krisna Irawan (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2021)
This study aims to determine the effect of using the Nike Training Club (NTC) application on increasing agility in STKIP Bina Mutiara basketball SMEs. The type of research used in this study is an experimental research design using One Group Pre-test Post-test Design. The instrument used by the Illinois Agility Test is to measure agility. The subjects of this study were 25 students who took part in basketball SMEs who were selected using a saturated sample. The results of data analysis showed an increase in agility (agility) in students who took part in SME basketball after getting treatment or treatment using the Nike Training Club application, as evidenced by the t value = 10,115 and the Sig value. 0.000 <0.05 means that it has a significant effect with a pre-test average of 19.40 and a post-test average of 15.80. Based on these results, it can be concluded for this study that there is an increase in the use of the Nike Training Club application on agility in STKIP Bina Mutiara basketball SMEs.